Heterotopic ossification on the volar surface of the distal radius in a child with fibrodysplasia ossificans progressiva: challenges in surgical excision of a rare condition - EROL, BÜLENT (ELSEVIER, 2021)
Fibrodysplasia ossificans progressiva (FOP) is one of the genetic and developmental forms of heterotopic ossification. We report a case of FOP on the volar surface of the distal radius, located close to the median nerve and radial artery with neurologic symptoms secondary to median nerve entrapment. The patient underwent surgical excision of the heterotopic lesion followed by radiation therapy. He had no signs of recurrence with more than 1 year of follow-up. Careful microsurgical dissection of the heterotopic mass must be performed to prevent the formation of new painful lesions and iatrogenic neurovascular injury. In this syndrome, the possibility of nerve entrapment due to the heterotopic lesion should be considered as the cause of neuropathic pain. Early genetic testing for confirmation of the suspected diagnosis can avoid having to do an unnecessary biopsy. (C) 2021 SFCM. Published by Elsevier Masson SAS. All rights reserved.
Keywords: Fibrodysplasia ossificans progressiva; Heterotopic ossification; Median neuropathy; Nerve dissection; Surgical excision